[Corrigendum] Information source and entrepreneurial performance expectations: Experience-based versus description-based opportunity evaluations - Pindard, Lejarraga, Maud; Lejarraga, José (Elsevier Inc., 2024)
How does the information source—experiential or descriptive—used by nascent entrepreneurs affect their performance expectations? Since judgments based on experience diverge from those based on descriptions,especially when prospects include a low-probability event such as entrepreneurial success,we argue that entrepreneurs’ expectations of success differ as a function of the information source they consult. We also contend that industry conditions interact with the information source to determine expectations. In two studies using field data from entrepreneurial settings,we found that experience generated lower expectations than did descriptions in unfavorable industry conditions (when success was a low-probability event). This pattern was reversed in favorable conditions (when success was more likely). Our findings provide field evidence consistent with the description–experience gap literature,thereby shedding new light on how nascent entrepreneurs’ informational environment shapes how they appraise business opportunities.
Keywords: Description–experience gap; Entrepreneurial performance expectations; Industry conditions; Opportunity evaluation; 53 Ciencias Económicas::5311 Organización y dirección de empresas; ODS 1 - Fin de la pobreza; ODS 5 - Igualdad de género; ODS 9 - Industria, innovación e infraestructura